Factors Affecting The Financial Behavior of Sme’s in Yogyakarta - Bangun Putra Prasetya; Nany Noor Kurniati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
After the Covid-19 pandemic, there began to be an improvement in economic life, especially for MSME players, especially in the Bakpia Center, Ngampilan, Yogyakarta. The improvement in economic conditions in MSMEs is also due to the pattern of financial behavior of MSME actors. Therefore, this study aims to analyze the factors that influence Financial Behavior. This research uses quantitative methods with analytical tools using SEM PLS. The results showed that the effect of Financial Self Efficiency on Financial Behavior showed that it was not significant. Financial Literacy and Incomeintention factors in this study show a significant influence on Financial Behavior